Premises of Foundation of a Deputy Head’s for Science Institution in Lithuanian Vocational Training System - Leliūgienė, Irena; Klimašauskienė, Rūta (Acta Paedagogica Vilnensia, 2001)
In the context of changes in educational field, a problem of quality of the management of an educational institution is becoming actual. This article deals with the following problem: can the foundation of an institution of deputy head for science in Lithuanian vocational training system optimise management of an institution for vocational training? The aim of the article is to overview premise of foundation of the deputy head’s for science institution in Lithuanian vocational training system. The article consists of two sections. The deputy head’s for science activity special features are analysed in the first section. In the second one, premise of foundation of the deputy head’s for science institution in Lithuanian vocational training system are discussed on the ground of an empirical research, carried out in Lithuanian vocational agricultural institution. The analysis of scientific literature revealed that the main features of the institution of deputy head for science, suggested by Moiseev and Moiseeva (1996), meet Western authors’ requirements for modem educational institution’s manager. The deputy head’s for science and the traditional deputy head’s for teaching activity differs. The deputy head’s for teaching activity is concentrated on organising teaching process. The deputy head’s for science activity is concentrated on the effective management of schools function and improving processes. The empirical research allow to draw a conclusion that the foundation of the deputy head’s for science institution in Lithuanian vocational training system can optimise the management of the vocational school, especially solving the following problems: the problem of training teachers inside the school and the problem of the school improvement through the instillation of novelties.